Homemade? An early 16th century carvel ship found in Oslo harbour, Norway - Vangstad, Hilde; Fawsitt, Sarah; Petrelius Grue, Marja-Liisa (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Bispevika 8 is the only wreck out of the 50 wrecks found in Oslo’s late medieval/early modern harbour that was carvel-built. Through documentation and analysis, it became clear that it is a 16th century Dutch-Flush built vessel. While the natural assumption would be that the ship was built in the Netherlands, elements of the construction, the provenance of the timber, results of the analysis of the waterproofing material, and written sources strongly indicate a local, Norwegian, place of origin.